Cu2AgInSe4 QDs sensitized electrospun porous TiO2 nanofibers as an efficient photoanode for quantum dot sensitized solar cells. (15th March 2020) - Kottayi, Roopakala; Panneerselvam, Pratheep; Murugadoss, Vignesh; Sittaramane, Ramadasse; Angaiah, Subramania
Graphical abstract: Highlights: Novel auspicious Cu2 AgInSe4 QDs are synthesized by a simple hot injection method. Porous TiO2 nanofibers (NFs) are developed by an electrospinning technique. Physicochemical properties of Cu2 AgInS4 QDs and porous TiO2 NFs are studied. Cu2 AgInSe4 QDs sensitized onto the P-TiO2 NFs is used as the photoanode for QDSC. The Photoconversion efficiency of 4.24% is obtained for the fabricated QDSC. Abstract: To obtain an efficient quantum dot sensitized solar cell (QDSC), a less toxic quaternary Cu2 AgInSe4 QDs with 4.8 nm in size are synthesized by a simple hot injection method. The crystallite size and tetragonal structure are confirmed by XRD and HR-TEM analysis. Energy-dispersive X-ray spectroscopy analysis reveals that the atomic ratio of Cu: Ag: In: Se in the Cu2 AgInSe4 QDs is 1.98:1.0:1.03:3.86. The oxidation state of the elements composed in Cu2 AgInSe4 QDs is confirmed by XPS studies. Optical properties are studied from the UV–Vis–NIR absorption spectrum and photoluminescence emission spectrum. The porous TiO2 nanofibers (P-TiO2 NFs) are prepared from the conventional electrospun TiO2 NFs followed by the solvosonication process. The FE-SEM analysis is confirmed the porous texture of the TiO2 NFs. The bandgap of the Cu2 AgInSe4 QDs and TiO2 NFs are determined from the Tauc plot and it was found to be 1.93 eV and 3.19 eV, respectively. QDSC is assembled using Cu2 S counter electrode, polysulfide redox couple electrolyte and Cu2 AgInSe4 QDs sensitized P-TiO2 NFs photoanode. The photoconversion efficiency (PCE) of the assembled QDSC is found to be 4.24%.